2005
DOI: 10.1097/01.ju.0000148941.57203.ec
|View full text |Cite
|
Sign up to set email alerts
|

Early Release of the Neurovascular Bundles and Optical Loupe Magnification Lead to Improved and Earlier Return of Potency Following Radical Retropubic Prostatectomy

Abstract: Minor modifications in nerve sparing technique lead to improved postoperative potency rates and decreased time to potency in men undergoing RRP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 11 publications
4
13
0
1
Order By: Relevance
“…The observed continuously decreasing incidence of rectal injuries over the years probably reflects not only increased surgeon experience but also the use of loupes and xenon head lights. This matches recently published experience from other centers [17] .…”
Section: Discussionsupporting
confidence: 80%
“…The observed continuously decreasing incidence of rectal injuries over the years probably reflects not only increased surgeon experience but also the use of loupes and xenon head lights. This matches recently published experience from other centers [17] .…”
Section: Discussionsupporting
confidence: 80%
“…Therefore, gentle and meticulous preservation, such as an early release of the NVB, is essential [76,77]. This approach has been previously reported to provide better functional recovery, raising the possibility of traction injury and/or poor visualization [76]. Moreover, our study showed that more nNOS-positive nerve fibers spread over the NVB to the 5-6 o'clock region in ED patients than in non-ED patients [75].…”
Section: Existing Clinical Features and Cn Distributionsupporting
confidence: 46%
“…In our study, the fibers increased at the apex and are possibly thinner in ED patients [75]. Therefore, gentle and meticulous preservation, such as an early release of the NVB, is essential [76,77]. This approach has been previously reported to provide better functional recovery, raising the possibility of traction injury and/or poor visualization [76].…”
Section: Existing Clinical Features and Cn Distributionmentioning
confidence: 89%
“…Since Walsh and Donker 4 published their landmark article describing the etiology and prevention of impotence following retropubic RP in 1982, the nerve-sparing technique they described is widely employed and believed to improve postoperative erectile function. 5 Furthermore, there continue to be modifications to the nervesparing technique in an attempt to minimize nerve compromise and improve postoperative potency, as reported by Chuang and coauthors 6 and Masterson and colleagues. 7 However, optimal sexual functioning often requires 18 to 42 months to return, even among men in whom bilateral nerve sparing was performed, with reported recovery rates varying from 16% to 86%.…”
Section: Résumémentioning
confidence: 95%